Effect of surface treatment on the mechanical properties of nickel-titanium files with a similar cross-section - Sang Won Kwak; Joo Yeong Lee; Hye-Jin Goo; Hyeon-Cheol Kim (Korean Academy of Conservative Dentistry, 2017)
Objectives The aim of this study was to compare the mechanical properties of various nickel-titanium (NiTi) files with similar tapers and cross-sectional areas depending on whether they were surface-treated. Materials and Methods Three NiTi file systems with a similar convex triangular cross-section and the same ISO #25 tip size were selected for this study: G6 (G6), ProTaper Universal (PTU), and Dia-PT (DPT). To test torsional resistance, 5 mm of the straightened file's tip was fixed between polycarbonate blocks (n = 15/group) and continuous clockwise rotation until fracture was conducted using a customized device. To evaluate cyclic fatigue resistance, files were rotated in an artificial curved canal until fracture in a dynamic mode (n = 15/group). The torsional data were analyzed using 1-way analysis of variance and the Tukey post-hoc comparison test, while the cyclic fatigue data were analyzed using the Mann-Whitney U test at a significance level of 95%. Results PTU showed significantly greater toughness, followed by DPT and G6 (p < 0.05). G6 showed the lowest resistance in ultimate torsional strength, while it showed a higher fracture angle than the other files (p < 0.05). In the cyclic fatigue test, DPT showed a significantly higher number of cycles to failure than PTU or G6 (p < 0.05). Conclusions Within the limitations of this study, it can be concluded that the torsional resistance of NiTi files was affected by the cross-sectional area, while the cyclic fatigue resistance of NiTi files was influenced by the surface treatment.